תאור השטטל ביצירות סופרים עבריים מאת עוזר לפרופ. עדנאן שביב ג'אסם Description of Shtetl in Works of Hebrew writers (Journal of the College of Languages (JCL), 2016)
מחקר זה עוסק בנושא (העיירה היהודית) שטטל ביצירותיהם של שני סופרים עבריים שהתמקדו בביקורת בשטטל. וזה נחשב להגבלה או למכשול לפיתוחם של היהודים, אז זה התרחש ביצירותיהם והם נתנו תשומת לב רבה לזה –לפי דעתם- גם זה נחשב להיבט בהיסטוריה והחיים של היהודים באירופה. סופרים עבריים רבים התעסקו בנושא השטטל שנהיתה לחומר ביצירותיהם. גם כן נהיתה אצל כמה מהם לשאלה חשובה, כי אם אנו מוצאים שיצירותיהם לא נטשו את האזכור של השטטל. דבר זה צפוי למצב הפרנסה הקשה שעמד בפני היהודים בשטטלים, ובגלל המדיניות שנתנהגו על ידי הממשלים האירופיים תוך כדי לרסן את העושר והשתלטותם של היהודים על הכלכלה של אותן מדינות. דבר זה הוביל לחולשת האפשרויות הכלכליות של היהודים שהביא אותם לבורות ולסיבה הזאת הופיעו התנועות הפוליטיות כמו הציונות, תנועות התחיה הלאומית, הדתיות והתרבותיות במו ההשכלה בתחילתה. שלום עליכם תיאר את השטטל בסיפורים רבים מסיפוריו, הוא תיאר את מצבה ומצב האוכלוסיה היהודית שחיה בה במיוחד העשירים שתיארם בצורה מצחיקה וסטירית. שלום עליכם היה משתמש בשמות וירטואליים לשטטלים וגם לאוכלוסיה. סיפוריו של ברדישבסקי התענינו ביחיד המורד על המסורת בשטטל, כנושא מרכזי כמו שמצאנו בסיפוריו, סיפורים אלה עסקו במציאות השטטל ומצב היהודים איפה חיים. הוא הותאם עם שלום עליכם בשאלת הצגת המציאות היהודית בשטטלים ובכפרים היהודים, אף על פי השתנות השיטה אלא שהמטרה היא אחת, שהיא הצגת המציאות היהודית ותיאורו בטרגי לגמרי.מההשוואה בין שני הסופרים מתברר שהשנים עסקו AbstractThis research deals with the subject of Shtetl (Jewish town) in the works of some Hebrew writers who focused on the criticism of this Shtetl and considered a restriction or an obstacle in front of the development of the Jews. Therefore It took space in their works and gave it great attention to it-by their point of view- considered an important part in the history and life of Jews in Europe.Many Hebrew writers took Shtetl and was subject of their works, and has been formed the important issue, we find their works didn’t abandoned mention of Shtetl. It is likely to the living situation, which was difficult that Jews faced in these Shtetls, because the policies of European governments to reduce their wealth, and control on the economic affairs in those countries. This affair led to the weakness of the Jew’s abilities, which led them to ignorance and illiteracy. These situations bring to appearance the political movements such as Zionism and nationalism movements, also the religious like Hasidic, and the cultural like Haskalah.Sholem Aleichem described Shtetl by many stories and the situation of Jews in these Shtetls. He talked about the economic situation of the population Jews in these Shtetls sociality the riches that he described them with irony and satire. Sholem Aleichem named the Shtetls and their peoples with virtual names.Berdyczewski’s stories took the recalcitrant Jew person upon Shtetl’s traditions as a central subject such as we find this issue in his stories. These stories deals with the reality of Shtetl and Jews situation where they lived. Berdyczewski’s coincided with Sholem Aleichem to view the Jewish reality in the Jewish towns, villages and Shtetls. In spite of different of the style, but the target is one to review the Jewish reality and imaging it as a tragic.Through comparative between two writers, become clear that they dealing with Shtetl as they think. So Berdyczewski focused on the salt and destructive reality in Shtetl. Sholem Aleichem focused on the ideology, culture and economic sides. He criticized the illiterate community whose had been grasped traditions.